Pengaruh Harga, Kualitas Produk Dan Promosi Terhadap Keputusan Pembelian Produk Sepatu Ortuseight Pada Toko Talago Sport Padang - Jerry Dwi Putra,; Khairil Aswan, (Jurnal Publikasi Ilmu Manajemen, 2023)
The purpose of this study is to test the price, product quality and promotion of the purchase decision of ortuseight shoe products at the Talago Sport Padang store This type of study uses quantitative methods, data collection through the distribution of questionnaires to 105 respondents using accidental sampling withdrawal techniques, namely probalitytechniques Sampling. By using instrument tests, (validity tests and reality tests), classical assumption tests (normality tests, multicollinearity tests and heteroschidasticity tests) then multiple linear regression and hypothesis tests with the help of SPSS applications. The results of the study show that price, product quality and promotion of the purchase decision of ortuseight shoe products at the talago sport padang store have a positive and significant effect on the purchase decision.